The positive impact of smoking on poor sleep quality is moderated by IGF1 levels in cerebrospinal fluid: a case-control study among Chinese adults - Shan, Ligang; Wu, Yuyu; Lao, Jiaying; Ma, Mingwei; Luo, Xingguang; Zheng, Ke; Hu, Weiming; Kang, Yimin; Wang, Fan; Liu, Yanlong; Xu, Yali; Jin, Xiaoya (Frontiers in Psychiatry, 2024)
Objective Previous research indicates associations between cigarette smoking, insulin-like growth factor-1 (IGF1), and sleep disturbances. This study aimed to examine the association between smoking and sleep quality and investigate the moderating role of IGF1. Methods This case-control study involved 146 Chinese adult males (53 active smokers and 93 non-smokers) from September 2014 to January 2016. Sleep quality and disturbances were evaluated using the Pittsburgh Sleep Quality Index (PSQI), which includes seven scales. Pearson correlation analysis and logistic regression analysis were utilized to examine the link between IGF1 levels in cerebrospinal fluid (CSF) and PSQI scores. The effect of IGF1 was assessed using the moderation effect and simple slope analysis, with adjustments made for potential confounders. Results Active smokers exhibited significantly higher global PSQI scores and lower IGF1 levels in CSF compared to non-smokers. A significant negative correlation was observed between IGF1 and PSQI scores (â = -0.28, P < 0.001), with a stronger association in non-smokers (Pearson r = -0.30) compared to smokers (Pearson r = -0.01). Smoking was associated with higher global PSQI scores (â = 0.282, P < 0.001), and this association was moderated by IGF1 levels in CSF (â = 0.145, P < 0.05), with a stronger effect at high IGF1 levels (Bsimple = 0.402, p < 0.001) compared to low IGF1 levels (Bsimple = 0.112, p = 0.268). Four subgroup analysis revealed similar results for sleep disturbances (Bsimple = 0.628, P < 0.001), with a marginal moderation effect observed on subjective sleep quality (Bsimple = 0.150, P = 0.070). However, independent associations rather than moderating effects were observed between IGF1 and sleep efficiency and daytime disturbance. Conclusion We provided evidence to demonstrate the moderation effect of IGF1 on the relationship between smoking and sleep in CSF among Chinese adult males.